"Slow down. Rail crossing ahead. Look left and right at the crossing": In-vehicle auditory alerts improve driver behavior at rail crossings. (January 2023) - Nadri, Chihab; Kekal, Siddhant; Li, Yinjia; Li, Xuan; Lee, Seul Chan; Nelson, David; Lautala, Pasi; Jeon, Myounghoon
Abstract: Even though the rail industry has made great strides in reducing accidents at crossings, train-vehicle collisions at Highway-Rail Grade Crossings (HRGCs) continue to be a major issue in the US and across the world. In this research, we conducted a driving simulator study ( N = 35) to evaluate a hybrid in-vehicle auditory alert (IVAA), composed of both speech and non-speech components, that was selected after two rounds of subjective evaluation studies. Participants drove through a simulated scenario and reacted to HRGCs with and without the IVAA present and through different music conditions and crossing devices. Driver simulator testing results showed that the inclusion of the hybrid IVAA significantly improved driving behavior near HRGCs in terms of gaze behavior, braking reaction, and approach speed to the crossing. The driving simulator study also showed the effects of background music and warning device types on driving performance. The study contributes to the large-scale implementation of IVAAs at HRGCs, as well as the development of guidelines toward a more standardized approach for IVAAs at HRGCs. Highlights: Train-vehicle collisions at highway-rail grade crossings (HRGCs) are still a major issue. 35 drivers participated in a driving simulator study with an in-vehicle auditory alert (IVAA). Participants drove scenarios with and without IVAA in different music and crossing conditions. The results show that IVAA significantly improved driving behavior and compliance at crossings. The study contributes to the implementation of IVAA at HRGCs and its standardization.